Analysis of Learning Difficulties in Multiplication and Division Operations with Porogapit in Fourth Grade Primary School Students - Afifah Nurfauzi, Ulfa; Wahyudin, (International Conference on Elementary Education, 2025)
This study aims to identify the learning difficulties of multiplication and division operations with porogapit experienced by fourth-grade students. This research used a qualitative approach with an exploratory descriptive method with 5 students as participants The instruments used were diagnostic tests and interview guidelines. Data collection was done through observation, interview and documentation techniques. The data were then analyzed through reduction, presentation, and inference. The results showed that overall the students understood the concept of stacked multiplication. Only a few minor errors and a lack of accuracy in working on problems were found. However, it is still seen that almost all the students have difficulties in stacked division, this is because the students do not understand the concept of division, are weak in remembering multiplication, and tend to rush and lack concentration when solving problems. Therefore, teachers should make sure that students understand the prerequisites of the division operation, and provide lots of practice, different teaching methods to help students understand the concept of division, and fun learning to arouse students' interest in learning mathematics. Consistency and thoroughness in providing guidance and support are also essential to overcome students' difficulties in solving division. With proper guidance and support, it is hoped that students can overcome these difficulties and perform well in mathematics.